Encapsulated Carbenoxolone Reduces Lung Metastases - Karsch-Bluman, Adi (Cancers (Basel), 2019)
Carbenoxolone is an anti-inflammatory compound and a derivate of a natural substance from the licorice plant. We previously showed that carbenoxolone reduces the metastatic burden in the lungs of mice through its antagonistic effect on high mobility group box 1 (HMGB1). To further enhance carbenoxolone’s activity and localization in the lungs, thereby reducing the potential adverse side effects resulting from systemic exposure, we developed a poly(lactic-co-glycolic acid) (PLGA) slow-release system for pulmonary delivery which maintains drug activity in-vitro, as demonstrated in the anoikis assay. Both systemic and intranasal administrations of carbenoxolone effectively minimize metastatic formation in a lung colonization model in mice. Our results show a decrease in the metastatic burden in the lung tissue. Notably, the therapeutic effect of a single intranasal administration of 25 mg/kg carbenoxolone, in the form of drug-loaded particles, had a similar effect in reducing metastatic lesions in the lungs to that of a 10-fold dose of the free drug via intraperitoneal injections, three times per week over the course of four weeks. These data offer new means to potentiate the anti-cancer activity of carbenoxolone and simultaneously reduce the requirement for high dosage administration; the upshot substantially improves therapeutic effect and avoidance of side effects.